fast track: Program 1000 HPK Dan Kejadian Stunting Berbasis Register Kohort Ibu Hamil Di Wilayah Kecamatan ‎Jangka Kabupaten Bireuen - Mursal, Mursal; Aramico, Basri; Maidar, Maidar; Abdullah, Asnawi; Hermansyah, Hermanyah (Jurnal Penelitian Kesehatan SUARA FORIKES, 2025)
Stunting is a global health issue of major concern, with the World Health Assembly (WHA) targeting a reduction in global prevalence from 7.8% to 5%. In Indonesia, data from the Basic Health Research (Riskesdas) indicate a decline in stunting prevalence from 37.2% in 2013 to 30.8% in 2018, although it remains above the threshold set by the WHO. The First 1,000 Days of Life (HPK) program serves as a key strategy in accelerating stunting reduction through interventions such as maternal nutrition fulfillment, complication prevention, child growth monitoring, and community education on nutrition and health. This study is a quantitative observational approach with a cross-sectional design, utilizing retrospective data collection from secondary sources, including the Maternal Cohort Database, Maternal and Child Health (KIA) Records, the Community-Based Electronic Nutrition Reporting System (EPPGBM), and the Indonesia Healthy Program with a Family Approach (PIS-PK). The study population comprises 480 mothers with children aged 24 months in 2024, selected through purposive sampling. To assess variable relationships, chi-square statistical analysis was applied as the primary method. The results indicate that several factors significantly correlate with stunting incidence, including maternal age during pregnancy (OR = 166.30; 95% CI = 64.03–431.92; p < 0.001), maternal nutritional status (OR = 168.15; 95% CI = 72.70–388.88; p < 0.001), iron-folic acid supplementation (OR = 658.41; 95% CI = 188.89–2294.93; p < 0.001), antenatal care (ANC) visits (OR = 1351.92; 95% CI = 299.94–6093.25; p < 0.001), pregnancy complications (p < 0.001), low birth weight (OR = 93.03; 95% CI = 46.32–186.83; p < 0.001), short birth length (OR = 2.62; 95% CI = 1.40–4.91; p = 0.003), exclusive breastfeeding (OR = 2.20; 95% CI = 1.28–3.78; p = 0.004), history of infectious diseases (OR = 4876; 95% CI = 880–26988; p < 0.001), and access to basic sanitation (OR = 1136.86; 95% CI = 53–8418; p < 0.001). Conversely, complete basic immunization (OR = 1.26; 95% CI = 0.35–4.53; p = 0.715), access to clean water (OR = 2.62; 95% CI = 0.57–11.92; p = 0.210), and household smoking habits (OR = 2.38; 95% CI = 0.53–10.52; p = 0.252) did not show significant associations with stunting. Maternal, neonatal, and environmental factors play a crucial role in stunting prevention, emphasizing the need for integrated health interventions to reduce stunting prevalence in the region. Additionally, evaluating the effectiveness of the First 1,000 Days of Life (HPK) Program and conducting community-based intervention trials, along with policy research at the local level, are essential for assessing the impact of government interventions.Keywords: 1000 HPK Program; Stunting; Maternal Cohort Database; EPPGBM‎